Reconhecimento e titulação de territórios quilombolas no Maranhão: especificidades da regularização fundiária da Comunidade Quilombola Boa Vista em Rosário - MA - CÂMARA, Conceição de Maria Silva (2024)
This dissertation was developed as an investigation into the Land Regularization of Quilombola Communities in Maranhão, specifically in the Quilombo of Boa Vista in Rosário - MA. The aim was to analyze how the historical, cultural specificities, and ways of life of the quilombolas were taken into account in the stages of land regularization carried out by ITERMA in that community. We sought to analyze the public policies accessed by the quilombolas after the start of the Land Regularization Process and after the Certification issued by the Palmares Cultural Foundation. The theoretical framework is based on the perspective of the Federal Constitution of 1988 and authors such as Santos, A. (2015), Gomes (2015), O’Dwyer (2002; 2008), Max Weber (2006), Almeida (1996; 2011), Oliveira Filho (1994), and others. Documentary research was conducted on the reports of the Occupational and Land Survey elaborated by ITERMA, as well as participant observation with semi- structured interviews with the quilombolas of Boa Vista. Therefore, it is concluded that Boa Vista has been in the land regularization process with ITERMA for 6 years. It was found that during the identification and demarcation process with the community, the quilombolas were protagonists of the narratives of their historical and sociocultural specificities, thus affirming the valorization of their ancestry. Additionally, Boa Vista began to access various public policies after its certification; however, the sluggishness of the land regularization process remains a problem experienced by the mentioned quilombolas.